Current project of management guidelines of the patients with nosocomial pneumonia in adults - Maria A. Karnaushkina; Andrey G. Maliavin; Leonid I. Dvoretckiy; Sergey V. Yakovlev; Sergey L. Babak; Sergey V. Fedosenko; Margarita P. Suvorova; Natalia F. Razgulyeva; Albina B. Arutyunova (Бюллетень сибирской медицины)
The nosocomial pneumonia is one of the most (or just “is a”) common hospital infections complicating the disease course and resulting in a fatal outcome. In 2016 the revised version of “Russian national recommendations for Nosocomial pneumonia in adults” was published. The new methods of diagnostics, preventative measures and hospital pneumonia treatment were systematized there. The international association of clinical pharmacologists and pharmacists introduced the new information on the epidemiology of hospital infections as well as their sensitivity to antibacterial therapy, dosage and introduction regime.  The current management guidelines of the patients with nosocomial pneumonia is based on these actual internationally recognized recommendations. It consists of an action algorithm to be used when the nosocomial pneumonia diagnosis is suspected and as tables which provide the tactics of treatment. It also helps to systematize the details of the anamneses, the data of functional and microbiological diagnostics and to develop an optimal scheme of empirical introduction of therapy and its further correction when necessary after receiving the results of microbiological diagnostics. The project is intended for physicians of internal medicine departments, emergency rooms in hospitals, as well as for resident medical practitioners. The quick introduction of management guideline algorithm of the patients with nosocomial pneumonia and the precise indication of the dose regime into clinical practice will allow doctors to decrease the death rate and improve the quality of medical service.